2017
DOI: 10.1007/s11060-017-2712-5
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based guided self-help for glioma patients with depressive symptoms: a randomized controlled trial

Abstract: Depressive symptoms are common in glioma patients, and can negatively affect health-related quality of life (HRQOL). We performed a nation-wide randomized controlled trial to evaluate the effects of an online guided self-help intervention for depressive symptoms in adult glioma patients. Glioma patients with depressive symptoms were randomized to a 5-week online course based on problem-solving therapy, or a waiting list control group. After having received the intervention, the glioma patient groups combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(135 citation statements)
references
References 46 publications
(45 reference statements)
1
134
0
Order By: Relevance
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The trials were published between 2005–2018. Trials were undertaken in the USA (Bantum et al, ; Owen et al, ; Smith et al, ; Somers et al, ; Syrjala et al, ), Netherlands (Admiraal et al, ; van der Berg et al, ; Boele et al, ; Golsteijn et al, ; Willems et al, ), UK (Foster et al, ), Canada (Vallerand et al, ), China (Zhang et al, ; Zhu et al, ), and South Korea (Lee et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants in four trials were patients with any cancer (Foster et al, ; Bantum et al, ; Somers et al, ; Willems et al, ). The other eleven trials focused on specific cancers: breast cancer (Admiraal et al, ; van den Berg et al, ; Lee et al, ; Owen et al, ; Smith et al, ; Zhu et al, ), glioma (Boele et al, ), haematological cancer (Syrjala et al, ; Vallerand et al, ), rectal cancer (Zhang et al, ), and both colorectal cancer and prostate cancer (Golsteijn et al, ). Nine trials reported participants who completed primary treatment (Admiraal et al, ; van der Berg et al, ; Foster et al, ; Lee et al, ; Bantum et al, ; Somers et al, ; Syrjala et al, ; Willems et al, ; Zhang et al, ); the time since treatment completion was 4 weeks to 18 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations